2021
DOI: 10.1159/000517197
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Regulation and Environmental Sex Determination in Cichlid Fishes

Abstract: Studying environmental sex determination (ESD) in cichlids provides a phylogenetic and comparative approach to understand the evolution of the underlying mechanisms, their impact on the evolution of the overlying systems, and the neuroethology of life history strategies. Natural selection normally favors parents who invest equally in the development of male and female offspring, but evolution may favor deviations from this 50:50 ratio when environmental conditions produce an advantage for doing so. Many specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 170 publications
0
8
0
Order By: Relevance
“…Other abiotic factors, such as salinity (Saillant et al, 2003) and pH (Reddon & Hurd, 2013) have also been shown to induce skewed sex ratios in fishes. This variety of SD systems within a recently speciated clade is not unprecedented; African cichlid fishes exhibit an enormous diversity of SD mechanisms, including several independently evolved sex chromosomes (Gammerdinger & Kocher, 2018; El Taher et al, 2021), polygenic GSD (Roberts et al, 2016), ESD (Renn & Hurd, 2021), and intraspecific variation in SD mechanisms (Lichilín et al, 2023). Further investigation into the forces underlying ESD in these and other species is warranted, as warming and acidifying oceans leave species whose gonadal differentiation are influenced by environmental factors much more vulnerable to impacts on sex ratios.…”
Section: Discussionmentioning
confidence: 99%
“…Other abiotic factors, such as salinity (Saillant et al, 2003) and pH (Reddon & Hurd, 2013) have also been shown to induce skewed sex ratios in fishes. This variety of SD systems within a recently speciated clade is not unprecedented; African cichlid fishes exhibit an enormous diversity of SD mechanisms, including several independently evolved sex chromosomes (Gammerdinger & Kocher, 2018; El Taher et al, 2021), polygenic GSD (Roberts et al, 2016), ESD (Renn & Hurd, 2021), and intraspecific variation in SD mechanisms (Lichilín et al, 2023). Further investigation into the forces underlying ESD in these and other species is warranted, as warming and acidifying oceans leave species whose gonadal differentiation are influenced by environmental factors much more vulnerable to impacts on sex ratios.…”
Section: Discussionmentioning
confidence: 99%
“…Other abiotic factors, such as salinity (Saillant et al, 2003) and pH (Reddon & Hurd, 2013) have also been shown to induce skewed sex ratios in fishes. This variety of SD systems within a recently speciated clade is not unprecedented; African cichlid fishes exhibit an enormous diversity of SD mechanisms, including several independently evolved sex chromosomes (El Taher et al, 2021; Gammerdinger & Kocher, 2018), polygenic GSD (Roberts et al, 2016), ESD (Renn & Hurd, 2021) and intraspecific variation in SD mechanisms (Lichilín et al, 2023). Given the possibility of inaccurate sex data and lack of genomic signal, further research is required to disentangle the roles of genotype and environment on sex in these species.…”
Section: Discussionmentioning
confidence: 99%
“…However, the success of reproductive performance, measured by means of fecundity, puberty onset, and sex reversal, can also have a high value from a retrospective point of view, as it is the end point of a complex cascade of developmental events that encompass a wide range of biotic and abiotic factors ( 18 22 ). In particular, the sex ratio in gonochoristic fish tends to be balanced in optimal culture conditions ( 23 ), although it can be affected by chemicals ( 24 ) and other environmental factors such as rearing density, temperature, pH, oxygen, and diet composition ( 25 29 ). Similarly, sex reversal in hermaphrodite species, such as in the protandrous gilthead sea bream, is socially controlled and endocrine-regulated by the circulating levels of estradiol (E 2 ) and 11-ketotestosterone (11-KT) ( 30 ), and intriguingly the exposure to synthetic estrogens (e.g., 17α-ethynylestradiol) prevents the male-to-female sex reversal ( 31 ).…”
Section: Introductionmentioning
confidence: 99%